Supraoptimal Iron Nutrition of Brassica napus Plants Suppresses the Iron Uptake of Chloroplasts by Down-Regulating Chloroplast Ferric Chelate Reductase - Sági-Kazár, Máté; Zelenyánszki, Helga; Müller, Brigitta; Cseh, Barnabás; Gyuris, Balázs; Farkas, Sophie Z.; Fodor, Ferenc; Tóth, Brigitta; Kovács, Béla; Koncz, Anna; Visnovitz, Tamás; Buzás, Edit I.; et al. (Frontiers in Plant Science, 2021)
Iron (Fe) is an essential micronutrient for plants. Due to the requirement for Fe of the photosynthetic apparatus the majority of shoot Fe content is localised in the chloroplasts of mesophyll cells. The reduction-based mechanism has prime importance in the Fe uptake of chloroplasts operated by Ferric Reductase Oxidase 7 (FRO7) in the inner chloroplast envelope membrane. Orthologue of Arabidopsis thaliana FRO7 was identified in the Brassica napus genome. GFP tagged construct of BnFRO7 showed integration to the chloroplast. The time scale expression pattern of BnFRO7 was studied under three different conditions: deficient, optimal and supraoptimal Fe nutrition both in leaves developed before and during the treatments. Although Fe deficiency has not increased BnFRO7 expression, the slight overload in the Fe nutrition of the plants induced significant alterations in both the pattern and extent of its expression leading to the transcript level suppression. The Fe uptake of isolated chloroplasts decreased both under Fe deficiency and supraoptimal Fe nutrition. Since the enzymatic characteristics of the ferric chelate reductase activity of purified chloroplast inner envelope membranes showed a significant loss for the substrate affinity with an unchanged saturation rate, protein level regulation mechanisms are suggested to be also involved in the suppression of the reduction-based Fe uptake of chloroplasts together with the saturation of the requirement for Fe.